Skeletal Age Assessment According to The Greulich and Pyle Atlas in Different Skeletal Malocclusions - Mevlüt Çelikoğlu; Doğan Kılkış; Mehmet Bayram; Metin Nur (Turkish Journal of Orthodontics, 2012)

(untitled)
Aim:To compare the skeletal age (SA) of the patients with and without different sagittal skeletal malocclusions of the jaws and to compare differences between males and females.Subjects and Methods:The sample comprised 120 patients (mean age 12.00±1.10) referred to our clinic. SA from the conventional roentgenograms of left hands and wrists by using the atlas of GP standards for each gender and skeletal class was estimated. The comparisons among the skeletal classes were done by means of the one way ANOVA test for both genders. Tukey post hoc test was used to determine the individual differences. The mean differences between the SA and chronological age (CA) of the subjects in each group were tested by means of paired t-test.ResultsMean SA for females with Class I, II, and III malocclusions were advanced 0.43, 0.22, and 0.61 years than mean CAs, respectively (P=0.051, P=0.228, and P=0.003). The mean difference between CA and SA for males with Class I, II, and III malocclusions were −0.14, −0.35, and 0.24 years, respectively (P=0.502, P=0.028, and P=0.088). The mean difference for males with Class II (−0.35±0.65) and Class III (0.24±0.59) malocclusions was statistically significant.Conclusion:These results suggest that patients with different skeletal malocclusions may have a different rhythm of skeletal maturation from that of children without malocclusions.